1995
DOI: 10.1172/jci117709
|View full text |Cite
|
Sign up to set email alerts
|

Anion secretion by the inner medullary collecting duct. Evidence for involvement of the cystic fibrosis transmembrane conductance regulator.

Abstract: It is well established that the terminal renal collecting duct is capable of electrogenic Na+ absorption. The present experiments examined other active ion transport processes in primary cultures of the rat inner medullary collecting duct. When the amiloride analogue benzamil inhibited electrogenic Na+ absorption, cAMP agonists stimulated a transmonolayer short circuit current that was not dependent on the presence of Na+ in the apical solution, but was dependent on the presence of Cl -and HCO -. This current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 39 publications
3
58
0
1
Order By: Relevance
“…In addition to the steroids, 1 mM 4-methylumbelliferyl-D-xyloside and 2.5 mM D(+)-galactosamine were added. We have found that these compounds greatly enhance the rate of seal formation (36), probably due to their ability to inhibit proteoglycan synthesis (37,38). Pilot studies have shown that they do not alter the qualitative response of the IMCD monolayers to steroids and that they retain their sensitivity to benzamil (data not shown).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition to the steroids, 1 mM 4-methylumbelliferyl-D-xyloside and 2.5 mM D(+)-galactosamine were added. We have found that these compounds greatly enhance the rate of seal formation (36), probably due to their ability to inhibit proteoglycan synthesis (37,38). Pilot studies have shown that they do not alter the qualitative response of the IMCD monolayers to steroids and that they retain their sensitivity to benzamil (data not shown).…”
Section: Introductionmentioning
confidence: 82%
“…The transmonolayer Isc and transepithelial resistance measurements were made in a modified Ussing chamber as previously described (1,2,36) on the day the cells were to be used. For each isolation used for mRNA analysis, parallel cultures were made in the large and the small Millicell filters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because CFTR functions not only as a Cl Ϫ channel, but also as a regulator of other cAMP-responsive apical membrane ion channels including the epithelial sodium channel (64,65), an outwardly rectifying chloride channel (28), and a renal potassium channel (66), we speculate that apical membrane resident CFTR Cl Ϫ channels serve at least two functions in distal nephron: first, mediation of transepithelial Cl Ϫ transport (14,15), and second, regulation of sodium chloride reabsorption/secretion as well as potassium secretion (64). Given that cAMP did not acutely stimulate CFTR trafficking in this study, it is unlikely that CFTR regulates these other ion channels by regulating their trafficking to the apical membrane.…”
Section: Table II Comparison Of I Sc In Parental and Gfp-cftr Expressmentioning
confidence: 99%
“…In contrast, little is known about the intracellular trafficking of CFTR or the mechanism(s) by which cAMP stimulates CFTRmediated Cl Ϫ secretion in kidney epithelia. Because CFTR Cl Ϫ channels are expressed in all nephron segments of the kidney (3) and are important for transepithelial Cl Ϫ transport (14,15) and enlargement of renal cysts in polycystic kidney disease (16), it is important to elucidate the role of cAMP in the regulation of CFTR in normal and pathophysiological renal states.…”
mentioning
confidence: 99%